Educating the Public Experiences - Bengkel Komuniti Air dan Kehidupan - Kem Pemimpin Muda Prihatin Air dan Program Reaching the Grassroots Peringkat Kebangsaan 2017 (Zon Timur) - Edriyana, Abd Aziz; Hasmanie, Abdul Halim; Fatimah, Ali (Penerbit UniMAP, 2018)
Malaysia is abundance with water resources. However, recently the water supply situation for the country has changed to one of scarcity (Ali et al., 2013). Population growth, urbanization, industrialization, and the expansion of irrigated agriculture have resulted in imposing demands, pressure on water resources as well as contributing to water pollution (WWDR, 2015). As water is crucial for our everyday lives, it is important to protect, conserve, and manage our water ethically. As one of the tertiary educational institutions in the East Coast region of Peninsular Malaysia, Universiti Malaysia Pahang (UMP) is responsible to share knowledge and skills to educate and raise the level of awareness of the community towards water resources sustainability